Endometrial stromal cells: isolation, expansion, morphological and functional properties - Zlatska, A.V.; Rodnichenko, A.E.; Gubar, O.S.; Zubov, D.O.; Novikova, S.N.; Vasyliev, R.G. (Experimental Oncology, 2017)
Aim: We aimed to study biological properties of human endometrial stromal cells in vitro. Materials and Methods: The endometrium samples (n = 5) were obtained by biopsy at the first phase of the menstrual cycle from women with endometrial hypoplasia. In all cases, a voluntary written informed consent was obtained from the patients. Endometrial fragments were dissociated by enzymatic treatment. The cells were cultured in DMEM/F12 supplemented with 10% FBS, 2 mМ L-glutamine and 1 ng/ml FGF-2 in a multi-gas incubator at 5% CO₂ and 5% O₂. At P3 the cells were subjected to immunophenotyping, multilineage differentiation, karyotype stability and colony forming efficiency. The cell secretome was assessed by BioRad Multiplex immunoassay kit. Results: Primary population of endometrial cells was heterogeneous and contained cells with fibroblast-like and epithelial-like morphology, but at P3 the majority of cell population had fibroblast-like morphology. The cells possessed typical for MSCs phenotype CD90⁺CD105⁺CD73⁺CD34⁻CD45⁻HLA⁻DR⁻. The cells also expressed CD140a, CD140b, CD146, and CD166 antigents; and were negative for CD106, CD184, CD271, and CD325. Cell doubling time was 29.6 ± 1.3 h. The cells were capable of directed osteogenic, adipogenic and chondrogenic differentiation. The cells showed 35.7% colony forming efficiency and a tendency to 3D spheroid formation. The GTG-banding assay confirmed the stability of eMSC karyotype during long-term culturing (up to P8). After 48 h incubation period in serum-free medium eMSC secreted anti-inflammatory IL-1ra, as well as IL-6, IL-8 and IFNγ, angiogenic factors VEGF, GM-CSF and FGF-2, chemokines IP-10 and MCP-1. Conclusion: Thus, cultured endometrial stromal cells meet minimal ISCT criteria for MSC. Proliferative potential, karyotype stability, multilineage plasticity and secretome profile make eMSC an attractive object for the regenerative medicine use.